2020
DOI: 10.3390/w12030738
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Simulation Study on Validating a Numerical Model for CO2 Density-Driven Dissolution in Water

Abstract: Carbon dioxide density-driven dissolution in a water-filled laboratory flume of the dimensions 60 cm length, 40 cm height, 1 cm thickness, was visualized using a pH-sensitive color indicator. We focus on atmospheric pressure conditions, like in caves where CO 2 concentrations are typically higher. Varying concentrations of carbon dioxide were applied as boundary conditions at the top of the experimental setup, leading to the onset of convective fingering at differing times. The data were used to validate a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Hence, the model solved in 2D can be viewed as a pseudo-3D approach. Class et al (2020) showed that this approach was able to reproduce experimental results in stagnant water satisfactorily.…”
Section: Model Setup and Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Hence, the model solved in 2D can be viewed as a pseudo-3D approach. Class et al (2020) showed that this approach was able to reproduce experimental results in stagnant water satisfactorily.…”
Section: Model Setup and Methodsmentioning
confidence: 91%
“…While the study of Michel-Meyer et al (2020) refers to processes in porous media, we remind that our focus here is primarily on open water bodies, where we have no such experimental data available. The modeling study presented below builds on a small experimental laboratory setup, previously used by Class et al (2020) under stagnant conditions for validating the numerical Navier-Stokes model which is briefly explained in Appendix A.…”
Section: Generic Scenario With Background Flow In a Small Laboratory Flumementioning
confidence: 99%
“…We chose the latter here. This approach has been applied successfully for a number of different applications with thin, slit‐like domains (Venturoli & Boek, 2006; Laleian et al., 2015; Kunz et al., 2015; Class et al., 2020). The channel is discretized with 30 cells in vertical and 133 cells in horizontal direction such that three grid cells coincide with one pore body at the interface.…”
Section: Evaporation From a Network Of Poresmentioning
confidence: 99%
“…This instability promotes CO 2 mixing due to convection, which is beneficial for the whole process. Beside CS, convective mixing is relevant to a wide range of other natural and industrial applications, such as enhanced oil recovery (EOR) (Kahrobaei et al, 2012;Sabet et al, 2018;Sheng, 2011), thermal and compositional mixing in the sea and oceanic water and karstification (Anderson et al, 1979;Ronen et al, 1988;Smith, 2004;Class et al, 2020), industrial chemical production (Wylock et al, 2014(Wylock et al, , 2017 and enhanced heat transfer using nanofluids (Heris et al, 2007;Li et al, 2003).…”
Section: Introductionmentioning
confidence: 99%